Sociology in the Clinic - Harvey Zorbaugh (Clinical Sociology Review)
The past twenty-five years have witnessed a great change in the behavior of sociologists. A quarter of a century ago the majority of sociologists might fairly have been labeled either philosophers or reformers. They dreamed on the one hand of cosmic cycles in the affairs of men; on the other hand, of utopia realized on earth. Today the great majority of sociologists —at least of the younger generation of sociologists —are scientists, attempting to develop methodology and techniques which will yield a greater understanding of, and, we may hope, control over a man’s social behavior.